Increasing patient participation in oncology clinical trials - Jie Chen; Ying Lu; Shivaani Kummar (Cancer Medicine)
Abstract Aim Timely recruitment of eligible participants is essential for the success of clinical trials, with insufficient accrual being the leading cause for premature termination of both oncology and non‐oncology trials. Methods In this paper we further elaborate on the challenges for patient participation in oncology trials from physician, patient, healthcare system, and some trial‐related perspectives. Results We present strategies such as use of digital healthcare technologies, real‐world data and real‐world evidence, decentralized clinical trials, pragmatic trial designs, and supportive services to increase patient participation. Conclusions Multifaceted measures are necessary to increase patient participation, especially for those who are under‐represented in cancer trials.